Gambaran Kadar Kalsium Serum Pada Lansia Di Kecamatan Sumber Kabupaten Cirebon - Usdiyanto Usdiyanto; Ikhawni Ikhawni; Oktafirani Al Sas (Lembaga Pengembangan Kinerja Dosen, 2024)
Metabolic processes in the body decrease with age. One of them occurs in calcium, when the age of more than 50 years, the amount of calcium in the body decreases by 30%. Meanwhile, if more than 70 years old, it decreases by about 50%. The imbalance of calcium levels in the body causes various diseases, one of which is osteoporosis. Osteoporosis occurs because the bones experience a decrease in bone mass due to lack of calcium intake in the body so that the body uses calcium reserves in the bones and teeth to meet calcium needs in the body. Because of the use of calcium in the bones, it causes the bones to lose mass so that they become porous, brittle, and even broken. One group that is prone to osteoporosis is the elderly. The purpose of this study was to determine serum calcium levels below normal values and the percentage of serum calcium levels below normal values in the elderly. The research method used was analytic survey, while the examination method used Cresolphtalein Complexone (CPC). The population in the study were 33 elderly aged 60 - 74 years in RW 03 Kaliwadas Village, Sumber District, Cirebon Regency. This study used a total sampling technique, so the sample used was the entire elderly population aged 60 - 74 years in RW 03 Kaliwadas Village. The research data were analyzed using the SPSS chi-square test program, and the value of Asymp. Sig. (2- Sided) is less than 0.05 which is 0.010. There are serum casium levels that are below normal values in the elderly with a percentage of 66.7%.